IMPLEMENTASI PERANCANGAN IDENTITAS VISUAL DALAM KONSER TALUN DI MUSEUM KOTA BANDUNG - Grace Carolline Sahertian (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2021)
The development of technology in this digital era affects various aspects of people's lives, including aspects of art and culture. Music, which is an element in art and culture, is also required to remain relevant to actual conditions. The emergence of video streaming platforms such as YouTube has an effect on decreasing public interest in enjoying live music performances. Therefore, music performances require a visual identity or visual branding as packaging that can build the image and attractiveness of the event. Konser Talun is a music show that is packed with creative concepts. The visual identity of Konser Talun was designed by adapting the elements found at the venue, namely Museum Kota Bandung. In addition, the visual elements are also adapted from the characteristics of the echo sound. Konser Talun’s visual identity design in the form of logos, colors, font selection and design elements, which are then applied to promotional media, visual backgrounds, lighting, installation and merchandise. The research method used is descriptive qualitative method with observation and interview instruments. In the end, this paper is expected to provide an overview of a comprehensive and holistic design process in designing the visual identity of a musical performance, which not only provides an audio-visual experience, but can also generate imagination and bind the audience's emotions, through interaction with all elements contained in Konser Talun.